Pengaruh Variasi Fraksi Volume Serat terhadap Kekuatan Bending dan Impak Komposit Polyester Berpenguat Serat Agave Cantula - Hendrikus Wona Wona; Kristomus Boimau; Erich U. K. Maliwemu (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2015)
Abstract The use of natural fibers as reinforcement material for natural fiber composite materials easily available, cheap, many types and variations. One of the natural fibers that can be used as reinforcement fiber composite is cantula agave plant leaves. In order to create a natural fiber composite material which has good mechanical properties, it should be known factors that affect the manufacture of the composite material. Factors that can affect the mechanical properties of the fiber composite material is fiber orientation, fiber composition, fiber volume fraction and volume fraction of the matrix. Fiber volume fraction is very large influence on the strength of the composite. This study aimed to determine the effect of fiber volume fraction on the bending strength and impact polymer composite reinforce cantula agave fiber with fiber volume fraction of 20%, 30% and 40%. The results showed that the bending and impact strength increases with increasing fiber volume fraction. Greatest bending obtained in the composite with 40% fiber volume fraction of 93.790 MPa and the lowest in the composite fiber volume fraction of 20% of 59.160 MPa, whereas for impact testing biggest impact on the composite with 40% fiber volume fraction of 0.159 Joules/mm2 and low impact strength obtained in composite fiber volume fraction of 20% amounting to 0.113 Joules/mm2.